Status quo of the will of Chinese professional volleyball players - Li, J.; Kang, H. (The Open Cybernetics & Systemics Journal, 2015)
The survey on the willpower of Chinese professional volleyball players shows that Chinese female volleyball players are more tenacious than male players, while male players are better in self-control.Willpower of volleyball players is independent with training duration and individual skill level of the players.The ace spiker is more clear in target than the setter and auxiliary setter; the setter is more confident than the auxiliary setter; the auxiliary setter is more resilient than the ace spiker and blocker; and the libero player is more resilient than the ace spiker, blocker, and setter, and more decisive than the ace spiker and setter. In this case, proper training and competition cognitive orientation is recommended to be established, with focus on the differences of players in gender, position, skill, and psychological quality. Perfect willpower qualities can be developed, including improving compression resistance intensity by training, and increasing difficulty tolerance by competition.